Liquid crystalline ordered arrays of gold nanoparticles in evaporative deposits. (21st September 2020) - Ahmad, Imtiaz; Jan, Rahim; Khan, Hidayat Ullah; Hussain, Akhlaq
Abstract: Gold nanoparticles assembly have been studied using two different evaporation techniques. To evaluate the influence CTAB molecules on self-assembly behavior 0.1 M CTAB suspension have been imaged via scanning helium ion microscopy (HIM) and then by SEM. By using immersion methode, dumbbell-like nanoparticles crystallizes over the substrate in island-like arrays showing no specific ordered structures whereas gold nanorods crystallizes in ordered arrays within the deposited islands. However, droplet drying showed aligned arrays of gold nanorods all over the coffee-stain ring. For purified suspensions, domain-like superstructures observed away from the outer-region of the coffee stain. These crystalline arrays grows into domain-like superstructures hydrodynamically.